Initial Trial Test of Potential Yield on 22 New Lines of Maize (Zea mays. L) - Ersyanda Yanuarsa; Andy Soegianto (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2022)
Corn (Zea mays L.) is an important food ingredient as one of the second carbohydrate producers after rice in Indonesia. The use of the corn plant is not only limited to the seeds, but other parts of the corn plant can also be used. To increase national maize production, intensification methods can be applied. One of the intensification activities can be realized by selecting planting materials obtained from crossing. The superior hybrid seeds can be obtained from intensive plant development and breeding activities. The purpose of this study was to determine the yield potential and characteristics of the new hybrid lines on the maize plant being tested. The research was conducted from January 2019 to May 2019 on an experimental plot owned by PT. BISI International Tbk. in Sambirejo Village, Bendo District, Kediri Regency. The design used in this experiment was a randomized block design with 2 replications. The number of treatments used consisted of 25 treatments with 22 new lines collected by PT. BISI International Tbk. and 3 comparison varieties such as BISI 18, NK6172 and P35. Observational variables observed included plant height (cm), plant vigor, flowering age of male plants (DAS), flowering age of female plants (DAS), harvest age (DAS), ear length (cm), moisture content (%), potential yield (tonnes / ha), seed yield (%), number of rows per ear, number of seeds per row, ear diameter (cm), percentage of seed filling (%), weight of 1000 seeds (g) and density (g / ml). The prospective hybrid candidates that have higher yield components than other hybrid lines are H6 and H11. The hopeful hybrid candidate excels in the potential outcome observation variables from the observed data.